Finding the hidden valence band of N = 7 armchair graphene nanoribbons with angle-resolved photoemission spectroscopy. (16th April 2018) - Senkovskiy, Boris V; Usachov, Dmitry Yu; Fedorov, Alexander V; Haberer, Danny; Ehlen, Niels; Fischer, Felix R; Grüneis, Alexander
Abstract: To understand the optical and transport properties of graphene nanoribbons, an unambiguous determination of their electronic band structure is needed. In this work we demonstrate that the photoemission intensity of each valence sub-band, formed due to the quantum confinement in quasi-one-dimensional (1D) graphene nanoribbons, is a peaked function of the two-dimensional (2D) momentum. We resolve the long-standing discrepancy regarding the valence band effective mass ( ) of armchair graphene nanoribbons with a width of N  =  7 carbon atoms (7-AGNRs). In particular, angle-resolved photoemission spectroscopy (ARPES) and scanning tunneling spectroscopy report   ≈0.2 and  ≈0.4 of the free electron mass ( m e ), respectively. ARPES mapping in the full 2D momentum space identifies the experimental conditions for obtaining a large intensity for each of the three highest valence 1D sub-bands. Our detail map reveals that previous ARPES experiments have incorrectly assigned the second sub-band as the frontier one. The correct frontier valence sub-band for 7-AGNRs is only visible in a narrow range of emission angles. For this band we obtain an ARPES derived effective mass of 0.4 m e, a charge carrier velocity in the linear part of the band of 0.63  ×  10 6 m s −1 and an energy separation of only  ≈60 meV to the second sub-band. Our results are of importance not only for the growing research field of graphene nanoribbons but also for the community, which studies quantum confined systems.